2008
DOI: 10.1073/pnas.0708100105
|View full text |Cite
|
Sign up to set email alerts
|

Starvation-dependent differential stress resistance protects normal but not cancer cells against high-dose chemotherapy

Abstract: Strategies to treat cancer have focused primarily on the killing of tumor cells. Here, we describe a differential stress resistance (DSR) method that focuses instead on protecting the organism but not cancer cells against chemotherapy. Short-term starved S. cerevisiae or cells lacking proto-oncogene homologs were up to 1,000 times better protected against oxidative stress or chemotherapy drugs than cells expressing the oncogene homolog Ras2 val19 . Lowglucose or low-serum media also protected primary glial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
496
3
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 509 publications
(564 citation statements)
references
References 34 publications
23
496
3
18
Order By: Relevance
“…As discussed in more detail later, in mice, fasting for 48-60 h increases protection from oxidative stress and protects three different strains of mice to etoposide, a drug known to promote oxidative stress, with remarkable improvement in survival compared with its normally fed counterparts (Raffaghello et al, 2008). In addition, 72-h of fasting protects the outbred CD-1 (Longo and Finch 2003a, b;Holehan and Merry, 1985) Required time 2-3 days (Raffaghello et al, 2008;Lee et al, 2010;Mitchell et al, 2009) Weeks-months (Longo and Finch 2003a, b;Fontana et al, 2010) Abbreviations: DR, dietary restriction; FFA, free fatty acid; GH, growth hormone; IGF-I, insulin-like growth factor 1; TG, triglycerides.…”
Section: Starvation and Stress Resistancementioning
confidence: 98%
See 3 more Smart Citations
“…As discussed in more detail later, in mice, fasting for 48-60 h increases protection from oxidative stress and protects three different strains of mice to etoposide, a drug known to promote oxidative stress, with remarkable improvement in survival compared with its normally fed counterparts (Raffaghello et al, 2008). In addition, 72-h of fasting protects the outbred CD-1 (Longo and Finch 2003a, b;Holehan and Merry, 1985) Required time 2-3 days (Raffaghello et al, 2008;Lee et al, 2010;Mitchell et al, 2009) Weeks-months (Longo and Finch 2003a, b;Fontana et al, 2010) Abbreviations: DR, dietary restriction; FFA, free fatty acid; GH, growth hormone; IGF-I, insulin-like growth factor 1; TG, triglycerides.…”
Section: Starvation and Stress Resistancementioning
confidence: 98%
“…In addition, 72-h of fasting protects the outbred CD-1 (Longo and Finch 2003a, b;Holehan and Merry, 1985) Required time 2-3 days (Raffaghello et al, 2008;Lee et al, 2010;Mitchell et al, 2009) Weeks-months (Longo and Finch 2003a, b;Fontana et al, 2010) Abbreviations: DR, dietary restriction; FFA, free fatty acid; GH, growth hormone; IGF-I, insulin-like growth factor 1; TG, triglycerides. Reduction in glucose and increased utilization of protein and lipid occur following both fasting and DR, but more pronounced in the former (Al-Regaiey et al, 2007;Felgines et al, 1999;Filaire et al, 2004;Lee et al, 2010;Menahan and Sobocinski 1983;Spindler et al, 1990;Wang et al, 2006).…”
Section: Starvation and Stress Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, an in vivo study showed that the treatment with 2-DG concomitantly with doxorubicin led to inhibition of apoptosis induced by this DNA-damaging drug in intestinal cells (Thakkar and Potten, 1993). Moreover, Regulation of tumor cell death by the glycolytic metabolism N El Mjiyad et al a differential effect of the influence of low glucose on chemotherapy resistance between normal and tumor cells has been observed (Raffaghello et al, 2008). Low glucose protected only primary glial cells, but not glioblastoma cancer cell lines, from cyclophosphamide.…”
Section: Chemoprotection Of Normal Tissues By 2-dg or Fastingmentioning
confidence: 99%